Oncologic outcomes of uterine preservation for pre-menopausal patients with stage II epithelial ovarian carcinoma. Issue 3 (March 2021) - Nasioudis, Dimitrios; Mulugeta-Gordon, Lakeisha; McMinn, Erin; Byrne, Maureen; Ko, Emily M; Cory, Lori; Haggerty, Ashley F; Latif, Nawar A
Abstract : Objective: Fertility-sparing surgery is rarely offered for patients with stage II epithelial ovarian carcinoma. The aim of the present study was to evaluate the overall survival of pre-menopausal patients with stage II epithelial ovarian carcinoma who did not undergo hysterectomy. Methods: The National Cancer Database was accessed, and patients aged ⩽40 years without a history of another tumor diagnosed between 2004 and 2015 with a pathological stage II epithelial ovarian carcinoma, who underwent lymphadenectomy and received multi-agent chemotherapy, were identified. Overall survival was compared with the log-rank test after generation of Kaplan–Meier curves. A Cox model was constructed to control for tumor histology. Results: A total of 185 patients met the inclusion criteria. The rate of uterine preservation was 24.3% (45 patients). Patients who did not undergo hysterectomy were younger (median 32 vs 37 years, p<0.001) and less likely to have high-grade tumors compared with those who underwent hysterectomy. The two groups were comparable in terms of presence of co-morbidities and performance of adequate lymphadenectomy (p>0.05). Median follow-up of the present cohort was 62.3 months (95% CI 53.6 to 71.0) and a total of 22 deaths occurred. There was no difference in overall survival between patients who did and did not undergo hysterectomy (p=0.50; 5-year overall survival rates 87.5% and 91.4%, respectively). After controlling for tumor histology, grade and substage, omission of hysterectomy was not associated with worse survival (HR 0.69, 95% CI 0.22 to 2.12). Conclusions: Uterine preservation was not associated with worse survival in this cohort of pre-menopausal patients with stage II epithelial ovarian carcinoma.